Dynamics of Foreign Workers from China in Indonesia: Guaranteeing Rights and Strengthening Legal Justice - Gultom, Yosua Saut Marulitua (HAPSc Policy Briefs Series, 2024)
The dynamics of the Asia Pacific are mainly influenced by China’s economic rise, which has a significant impact on bilateral relations with Indonesia. China’s economic revival, supported by economic transformation and control of strategic sectors, has made it a global economic power. Indonesia as the de facto leader of ASEAN has historical ties with China, which are further strengthened through strategic partnerships. Large investments from China within the framework of the Belt and Road Initiative (BRI) have triggered an increase in the flow of Chinese foreign workers in Indonesia. This, while supporting economic growth, also raises concerns regarding competition with the domestic workforce and social justice. Using a descriptive qualitative approach, this research tries to describe the dynamics of Chinese foreign workers in Indonesia by focusing on the role of the DPR RI as a supervisory and regulatory institution in dealing with this issue. The importance of strengthening the capacity of domestic workers to compete with foreign workers, transferring useful knowledge, and regulations that protect labor rights, especially in the face of international competition, is the main essence of why special attention is needed in handling the impact of the presence of foreign workers. Strengthening immigration controls is also crucial to avoid potential violations and create a fair situation for domestic and foreign workers. Data harmonization between government agencies and cooperation with China are necessary to achieve a conducive and mutually beneficial situation for both parties. It is hoped that this research can contribute to thinking and policy direction in managing the impact of the presence of foreign workers in Indonesia.